Upregulation of galectin-3 in immortalized Schwann cells IFRS1 under diabetic conditions. (March 2015) - Tsukamoto, Masami; Sango, Kazunori; Niimi, Naoko; Yanagisawa, Hiroko; Watabe, Kazuhiko; Utsunomiya, Kazunori
Highlights: High glucose and 3-DG upregulated the expression of GAL-3 in IFRS1 Schwann cells. Aminoguanidine and resveratrol attenuated the high glucose-induced GAL-3 upregulation. Recombinant GAL-3 suppressed 4HNE expression and enhanced Bcl-2 expression. GAL-3 may play a cytoprotective role in Schwann cells under diabetic conditions. Abstract: A spontaneously immortalized adult Fischer rat Schwann cell line IFRS1 retains the characteristic features of normal Schwann cells, and can be a useful tool for the study of diabetic neuropathy. In the present study, we examined the effects of high glucose and 3-deoxyglucosone (3-DG) on the viability and the protein expression of advanced glycation endproducts (AGE)-binding proteins, such as galectin-3 (GAL-3) and receptor for AGE (RAGE) in IFRS1 cells. Exposure to 30 mM of glucose or 0.2 mM of 3-DG for 7 days failed to impair the IFRS1 cell viability, but significantly upregulated the expression of GAL-3. The same exposure tended to increase the expression of RAGE, but the changes were not significant. The high glucose-induced upregulation of GAL-3 was attenuated by cotreatment with 0.2 mM of an anti-glycated agent aminoguanidine or 20 nM of an anti-oxidant trans-resveratrol. In addition, treatment of IFRS1 cells with 1 μg/ml of recombinant GAL-3 for 48 h resulted in the upregulation of B-cell lymphoma 2 (Bcl-2) and the downregulation of 4-hydroxynonenal (4HNE). These findings suggest the involvement of GAL-3 in the glycation and oxidative stress under diabetic conditions and its cytoprotective role in Schwann cells.